Does it pay to go public? Understanding the public-private sector wage gap in Germany - Marina Bonaccolto-Töpfer; Carolina Castagnetti; Stephanie Prümer (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2021)
Using data from the German Socio-Economic Panel 1984-2017, this paper provides first evidence on the public-private sector wage gap in Germany based on a fixed effect quantile approach. The results reveal substantial differences in the decomposition of the gap compared to the standard cross-sectional approach. We find that women earn more in public employment, while men are penalized. Our analysis suggests that this penalization is not related to compensating wage differentials. Against the background of demographic change, the public sector may face difficulties to recruit (skilled) men and may need to adjust its pay schemes to fair and merit-based ones. – – Mit Daten des Sozioökonomischen Panels 1984-2017 untersucht dieser Beitrag die Lohnlücke zwischen dem öffentlichen und privaten Sektor in Deutschland und liefert dabei erste Evidenz, die auf einem Quantilsansatz mit fixen Effekten beruht. Mit diesem Ansatz finden wir substantielle Unterschiede in der Zerlegung der Lohnlücke im Vergleich zum Standard-Querschnittsansatz. Demnach verdienen Frauen im öffentlichenSektor mehr, während Männer benachteiligt werden. Unsere Analyse legt nahe, dass diese Benachteiligung nicht mir kompensierenden Lohndifferentialen zusammenhängt. Vor dem Hintergrund des demografischen Wandels könnte der öffentliche Sektor daher Probleme haben, (qualifizierte) Männer zu rekrutieren, und sollte seine Entlohnungssysteme fair und leistungsorientiert gestalten.
Keywords: J31; J45; C33; 330; Public-Private Sector Wage Gap; Quantile Regression for Panel Data; Germany